2022
DOI: 10.1111/1759-7714.14321
|View full text |Cite
|
Sign up to set email alerts
|

circFIG 4 drives the carcinogenesis and metastasis of esophagus cancer via the miR‐493‐5p/E2F3 axis

Abstract: Background: Esophageal cancer (EC) is a highly malignant tumor of the digestive tract. Circular RNAs (circRNAs) have been verified to play a regulatory role in the occurrence and progression of different cancers, including EC. This research aimed to investigate the role and molecular mechanism of circFIG 4 in EC progression. Methods: The analyses of circFIG 4, miR-493-5p, and neuro-oncological ventral antigen 2 levels were administrated by quantitative real-time polymerase chain reaction. The characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Several studies have shown that miR‐493‐5p has antitumor functions in various cancer types. Although miR‐493‐5p has been reported to function in a suppressive manner in various cancer types, 27 , 28 , 29 it has not been reported in cholangiocarcinomas, including ICC. The expression patterns and biological mechanisms of miR‐493‐5p in ICC progression have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that miR‐493‐5p has antitumor functions in various cancer types. Although miR‐493‐5p has been reported to function in a suppressive manner in various cancer types, 27 , 28 , 29 it has not been reported in cholangiocarcinomas, including ICC. The expression patterns and biological mechanisms of miR‐493‐5p in ICC progression have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Not more than that, the same miRNA can be regulated by different epigenetic mechanisms. For example, miR-493-5p, is dramatically downregulated in ESCC tissues and cells due to “sponging” from both circFIG4 and linc00324, both of which modulated ESCC progression including ESCC cell invasion and migration via targeting the miR-493-5p/E2F3 and miR-493-5p/MAPK1 axis, respectively[ 145 - 147 ]. Another example, miR-124-3p, was found to have positive correlations with ESCC invasion and migration, as well as EMT via the regulation of lncZFAS1 and through DNA methylation[ 31 , 127 ].…”
Section: Epigenetics Effects On Mirnas In Escc Metastasismentioning
confidence: 99%
“…Normally found upregulated, circFIG4 promotes cell cycle activity through sponging miR-493-5p, releasing E2F3 from being repressed [ 124 ]. Interestingly, circFNDC3B and hsa_circ_00014879 (circDCAF8) positively influence the same downstream target, CDC25A.…”
Section: Circrna and Cell Cycle Regulators In Cancermentioning
confidence: 99%